Direito à cidade sustentável: construindo o “bem viver” urbano a partir da justiça socioambiental e da cidadania ecológica - Mattos, Daniela Favaretto (2020)
The brazilian urban space presents numerous socio-environmental vulnerabilities, due to the economic development model adopted which determined the violation of fundamental human rights in search of material progress. Cities became centers of production and consumption, with citizens and their yearnings silenced, resulting in the current situation of urban unsustainability. Thus, it is necessary to build a new urban space, in which quality of life and human dignity are prioritized, balancing social, environmental, territorial, economic, political, ethical and legal demands, guaranteeing, also, the right that all citizens have to live in a sustainable city. In this line, this work intends to make a theoretical analysis of the construction of “Bem Viver” based on elements that guarantee socio-environmental justice and ecological citizenship in the search for the realization of the right to a sustainable city in the brazilian urban scenario. The work seeks to answer, therefore, the following question: What are the limits and possibilities for the realization of the right to a sustainable city characterized by the urban “Bem Viver” from elements that guarantee socio-environmental justice and ecological citizenship in Brazil? To answer this question, the methodology and action strategy to make this research feasible obey the trinomial: Base Theory/Approach, Procedure and Technique. As an approach, we chose the systemic-complex perspective to configure a method that allows an interdisciplinary research approach and in synergy with different areas of knowledge (Social, Applied Social Sciences, Human Sciences, Network Technologies and Information and Communication Technologies). The procedure used consists of bibliographic and documentary analysis (in physical and digital media). The technique employed is limited to the production of records, extended abstracts, tables for systematizing the data and information obtained. Thus, it is concluded that the realization of the right to a sustainable city still finds limits, which can be divided into three main axes: economic, political and social. The first consists of the capitalist economic development model adopted by the cities, the second comprises the absence of public policies for the reduction of socio-environmental vulnerabilities and the third involves the reduced popular participation in decisions that involve community life. However, there are also possibilities for realizing the right to a sustainable city, which can overcome these limits. The first consists of the adoption of the sustainable development model in cities, the second comprises the implementation of public policies aimed at addressing the issues surrounding the main vulnerabilities observed in the urban space, promoting socio-environmental justice, and the third involves the provision of tools that allow access to information, allowing the ecologically emancipated citizen to actively participate in the construction of this new urban space.